REKAYASA PERANGKAT LUNAK PERHITUNGAN GERAK LURUS FISIKA BERBASIS ANDROID (Information Technology and Telematics, 2013)
Physics is the science or knowledge about nature in the widest sense. Physics learn about natural phenomena that do not live material within the scope of space and time. The Physicists learn about the behavior and characteristic in many areas, starting from microscopic particles that make up all material (Particle Physics) until behavior of the material universe as a whole cosmos.  This application consist of calculate rectilinear motion, calculate accelerated motion, calculate the upward vertical motion, calculate the downward vertical motion. The result of this applications is, calculate the physicsbased motion straight android to suit the learning process to the students in a straight motion physics calculations.Keywords: Physics, Rectilinear Motion, Calculate, Android